2017
DOI: 10.1111/ans.14233
|View full text |Cite
|
Sign up to set email alerts
|

Lower risk of pelvic metalware infection with operative repair of concurrent bladder rupture

Abstract: Operative repair of bladder rupture is associated with a lower rate of pelvic orthopaedic hardware infection in the presence of concurrent pelvic fracture requiring internal fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Other factors as the history of pelvic embolisation, pelvic packing, use of external fixators/C-Clamps, the presence of a suprapubic catheter, or of Morel-Lavallee lesions or the large number of transfusions and evidence of post-traumatic immunoparesis were not confirmed in this study in contrast to the previous reports. [ 44 49 ]. These differences could be attributed to the small incidence of SSI in our cohort, leaving only 18 cases of recorded deep infection to analyse.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors as the history of pelvic embolisation, pelvic packing, use of external fixators/C-Clamps, the presence of a suprapubic catheter, or of Morel-Lavallee lesions or the large number of transfusions and evidence of post-traumatic immunoparesis were not confirmed in this study in contrast to the previous reports. [ 44 49 ]. These differences could be attributed to the small incidence of SSI in our cohort, leaving only 18 cases of recorded deep infection to analyse.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective cohort of 45 bladder trauma patients, the authors reported lower rate of pelvic hardware infection in patients managed with surgical repair than those managed nonoperatively (33% vs. 5.6%, P = .047). 25 However, when only comparing the patients with EBIs (n = 28), this difference did not reach statistical significance ( P = .08). Of note, only 5 patients in this series had pelvic hardware infection with 2 of them being in the surgical repair cohort, emphasizing the lack of statistical power and the narrow margin for the results to be changed in either direction with 1 or 2 cases.…”
Section: Reviewmentioning
confidence: 89%
“…Of note, only 5 patients in this series had pelvic hardware infection with 2 of them being in the surgical repair cohort, emphasizing the lack of statistical power and the narrow margin for the results to be changed in either direction with 1 or 2 cases. 25 In another retrospective review of 80 EBI patients, Johsnsen et al suggested that overall complication rates and hospital stay were lower in EBIs that were surgically repaired at the time of other nonurologic interventions than those who underwent interventions without fixing the bladder. 13 However, only 1 of the 28 patients who underwent ORIF had a pelvic hardware infection, so no conclusion can be reached on the rate of orthopedic complications and the role of concomitant bladder surgery at the time of ORIF based on these data.…”
Section: Reviewmentioning
confidence: 99%
“…Extra-peritoneal bladder ruptures can be managed non-operatively with catheter drainage alone. 3,4,10,[21][22][23][24] Indications for operative repair of EBR include: failure of conservative management 1,21 ; the presence of associated vaginal, 1,21 prostate 21 or rectal injury 1,22,24 ; involvement of the bladder neck 1,21,22,24 ; bony fragments present within the bladder wall 22,24 ; laparotomy for an additional indication 1,21,22 ; fracture pelvis requiring internal fixation 1,22,24,27,28 ; or a penetrating injuries. 1,21,22 In our cohort, the high incidence of concurrent injuries requiring operative intervention accounted for the high rates of intraoperative repair (56.2%) for our patients with EBR.…”
Section: Discussionmentioning
confidence: 99%